2022
DOI: 10.1159/000521746
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data for Lenvatinib in Hepatocellular Carcinoma (ELEVATOR): A Retrospective Multicenter Study

Abstract: Background Lenvatinib is approved as first-line treatment for patients with advanced hepatocellular carcinoma (HCC). The efficacy of lenvatinib in Caucasian real-world patients is insufficiently defined. The purpose of this study was to evaluate the efficacy of lenvatinib in a multi-center cohort (ELEVATOR) from Germany and Austria. Methods A retrospective data analysis of 205 patients treated with first-line systemic lenvatinib at 14 different sites was conducted. Overall survival, progression free survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…This is consistent with recently published data on the use of atezolizumab plus bevacizumab [ 21 ] in first-line treatment. Nevertheless, multivariate Cox regression identified liver function (ALBI score) as the strongest prognostic marker in our cohort, underscoring the known effect of liver function in determining prognosis in these patients [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…This is consistent with recently published data on the use of atezolizumab plus bevacizumab [ 21 ] in first-line treatment. Nevertheless, multivariate Cox regression identified liver function (ALBI score) as the strongest prognostic marker in our cohort, underscoring the known effect of liver function in determining prognosis in these patients [ 22 , 23 ].…”
Section: Discussionsupporting
confidence: 54%
“…This proves that lenvatinib can still provide a favorable efficacy, even for patients who do not meet the REFLECT criteria. A similar result was also demonstrated in patients with advanced HCC in the study of Welland et al [ 38 ], despite the fact that some surgically treated patients were included. When lenvatinib was compared with sorafenib, unlike the previous phase III clinical trial that showed no significant difference in OS, our meta-analysis showed that lenvatinib could significantly improve OS and PFS and offer better ORR and DCR.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we assessed the effects of LINC01468 on lenvatinib (LVB) and sorafenib (SOR) sensitivity. Sorafenib was the first multi-tyrosine kinase inhibitor approved for the treatment of patients with unresectable HCC [ 25 ], while lenvatinib is another tyrosine kinase inhibitor that received approval for first-line treatment of patients with advanced HCC [ 26 ]. LINC01468 silencing sensitized SNU-449 cells to LVB, as reflected by a reduction in cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%